Rapid and efficient isolation platform for plasma extracellular vesicles: EV‐FISHER - Wei‐Lun Pan; Jun‐Jie Feng; Ting‐Ting Luo; Yong Tan; Bo Situ; Rienk Nieuwland; Jing‐Yun Guo; Chun‐Chen Liu; Han Zhang; Jing Chen; Wen‐Hua Zhang; Jun Chen; et al. (Journal of Extracellular Vesicles, 2022)
Abstract Extracellular vesicles (EVs) have found diverse applications in clinical theranostics. However, the current techniques to isolate plasma EVs suffer from burdensome procedures and limited yield. Herein, we report a rapid and efficient EV isolation platform, namely, EV‐FISHER, constructed from the metal‐organic framework featuring cleavable lipid probes (PO43−‐spacer‐DNA‐cholesterol, PSDC). The EV‐FISHER baits EVs from plasma by cholesterol and separates them with an ordinary centrifuge. The captured EVs could be released and collected upon subsequent cleavage of PSDC by deoxyribonuclease I. We conclude that EV‐FISHER dramatically outperforms the ultracentrifugation (UC) in terms of time (∼40 min vs. 240 min), isolation efficiency (74.2% vs. 18.1%), and isolation requirement (12,800 g vs. 135,000 g). In addition to the stable performance in plasma, EV‐FISHER also exhibited excellent compatibility with downstream single‐EV flow cytometry, enabling the identification of glypican‐1 (GPC‐1) EVs for early diagnosis, clinical stages differentiation, and therapeutic efficacy evaluation in breast cancer cohorts. This work portrays an efficient strategy to isolate EVs from complicated biological fluids with promising potential to facilitate EVs‐based theranostics.